2020
DOI: 10.1242/dev.191411
|View full text |Cite
|
Sign up to set email alerts
|

Using Drosophila to drive the diagnosis and understand the mechanisms of rare human diseases

Abstract: Next-generation sequencing has greatly accelerated the discovery of rare human genetic diseases. Nearly 45% of patients have variants associated with known diseases but the unsolved cases remain a conundrum. Moreover, causative mutations can be difficult to pinpoint because variants frequently map to genes with no previous disease associations and, often, only one or a few patients with variants in the same gene are identified. Model organisms, such as Drosophila, can help to identify and characterize these ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 90 publications
0
32
0
Order By: Relevance
“…Development from embryo to adult takes about 10 days and adult lifespan 1–2 months ( Johnson and Stolzing, 2019 ), allowing metabolic investigations on hundreds of offspring either at juvenile (larva and pupa) or adult stages. Given its powerful genetics, the Drosophila model has proved an efficient strategy for the study of several types of human pathologies, including metabolic ( Perrimon et al, 2016 ; Musselman and Kuhnlein, 2018 ; Baenas and Wagner, 2019 ), neurological ( Coll-Tane et al, 2019 ; Link and Bellen, 2020 ; Mariano et al, 2020 ; Salazar et al, 2020 ), cardiac ( Birse et al, 2010 ; Piazza and Wessells, 2011 ; Diop et al, 2015 ; Guida et al, 2019 ), digestive ( Musselman and Kuhnlein, 2018 ; Nayak and Mishra, 2019 ), and nephrocytic ( Millet-Boureima et al, 2018 ; Rani and Gautam, 2018 ) comorbidities. In addition, tumor models may be induced in larvae or adult flies by genome manipulation ( Pagliarini and Xu, 2003 ; Igaki et al, 2006 ; Dong et al, 2007 ; Gonzalez, 2013 ; Hirabayashi et al, 2013 ; Samji et al, 2021 ).…”
Section: The Fruit-fly Modelmentioning
confidence: 99%
“…Development from embryo to adult takes about 10 days and adult lifespan 1–2 months ( Johnson and Stolzing, 2019 ), allowing metabolic investigations on hundreds of offspring either at juvenile (larva and pupa) or adult stages. Given its powerful genetics, the Drosophila model has proved an efficient strategy for the study of several types of human pathologies, including metabolic ( Perrimon et al, 2016 ; Musselman and Kuhnlein, 2018 ; Baenas and Wagner, 2019 ), neurological ( Coll-Tane et al, 2019 ; Link and Bellen, 2020 ; Mariano et al, 2020 ; Salazar et al, 2020 ), cardiac ( Birse et al, 2010 ; Piazza and Wessells, 2011 ; Diop et al, 2015 ; Guida et al, 2019 ), digestive ( Musselman and Kuhnlein, 2018 ; Nayak and Mishra, 2019 ), and nephrocytic ( Millet-Boureima et al, 2018 ; Rani and Gautam, 2018 ) comorbidities. In addition, tumor models may be induced in larvae or adult flies by genome manipulation ( Pagliarini and Xu, 2003 ; Igaki et al, 2006 ; Dong et al, 2007 ; Gonzalez, 2013 ; Hirabayashi et al, 2013 ; Samji et al, 2021 ).…”
Section: The Fruit-fly Modelmentioning
confidence: 99%
“…Missense DNMs in particular present a unique challenge because most genes lack established functional assays. Drosophila melanogaster is a genetically tractable system that is widely used to study human diseases [10][11][12] . In addition to studying disease mechanisms by establishing preclinical models, flies can be used as a 'living test tube' to study functional consequences of variants of unknown significance found in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Missense DNMs in particular present a unique challenge because most genes lack established functional assays. Drosophila melanogaster is a genetically tractable system that is widely used to study human diseases [10][11][12] . Here, we integrate a number of state-of-the-art technologies in the fly field to establish an in vivo pipeline to effectively study the functional impact of DNMs identified in a large cohort of ASD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic engineering technologies in Drosophila melanogaster have greatly advanced the study of basic biology and human disease ( Bier, 2005 ; Venken and Bellen, 2007 , 2014 ; Venken et al, 2016 ; Bellen et al, 2019 ; Link and Bellen, 2020 ). Historically, germline genetic manipulations in fruit flies, e.g., insertional mutagenesis and transgenesis, almost exclusively relied on P element transposons ( Ryder and Russell, 2003 ).…”
Section: Introductionmentioning
confidence: 99%